2019
DOI: 10.2478/amset-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency – Sentiment Analysis in Social Media

Abstract: The paper proposes the exploration, identification and development of a Java solution for extracting the sentiment related to the cryptocurrencies phenomenon, from the content of the posts of certain popular social networks. Detecting the positive, neutral or negative character of the sentiment is adopted as a relevant method of establishing the nature of the human perception on the topical issue defined by cryptocurrencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Cryptocurrency prices typically decline when news or social media posts have a negative tone and vice versa [22]. One of the earliest works is presented in [23], which used IBM Watson and Stanford CoreNLP to analyze the sentiment of Reddit and Twitter users. It is reported that sentiment captured from both social media sources contributed to cryptocurrency price change in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptocurrency prices typically decline when news or social media posts have a negative tone and vice versa [22]. One of the earliest works is presented in [23], which used IBM Watson and Stanford CoreNLP to analyze the sentiment of Reddit and Twitter users. It is reported that sentiment captured from both social media sources contributed to cryptocurrency price change in the market.…”
Section: Introductionmentioning
confidence: 99%